Application of interspecific sesquiploidy to introgression of PLRV resistance from non-tuber-bearing Solanum tuberosum to cultivated potato germplasm - Chavez, R.; Brown, CR; Iwanaga, Masaru (Springer, 1988)
Hybridization of synthetic allotetraploids of S. pinnatisectum with S. etuberosum (4x-EP) with S. acaule (2n = 4x = 48) resulted in two individuals that were highly fertile, in contrast to all other progenies. The unique individuals are hexaploids, 2n = 72, while the other progenies are tetraploids, 2n = 48. They are thought to be the products of a union between 2n eggs of S. acaule and normal 1n microspores of 4x-EP. The fertile hexaploids (designated 6x-AEP) produced abundant selfed seed and viable hybrids with cultivated diploid potato, S. phureja, when developing embryos were rescued from berries and cultured before transplanting to pot culture. The extreme variability in chromosome constitution of the hybrids with S. phureja and selfed progenies indicates that addition and substitution lines of etb chromosomes bearing genes of interest to breeders could easily be produced from this material. The production of sesquiploids, as the 6x-AEP hybrids are called, is discussed as a useful bridging step in the introduction of alien genes from genomes that share little homology with the cultivated genome.